The water shell in the rural area: water consumption under the perspective of the farmers of a settlement in the municipality of Pombal-PB (Research, Society and Development, 2019)
Water scarcity is a growing problem and is already affecting the entire planet, which is worsening in semi-arid regions. Thus the main objective of this research was to verify the water consumption situation and the perception of the settlers regarding the water issue in the Santa Mônica settlement, located in the rural area of the municipality of Pombal, in the upper Sertão of Paraíba. As a result it was possible to identify that, despite the good housing with which they were contemplated, there is no type of education and health structure, and no water source within the settlement. Residents are mostly fueled by caravans and do not trust the quality of this water, but do not take care to treat it before consuming. Its average daily consumption is approximately 70 to 93 liters per person, which indicates consumption below what is suggested by the UN, in order to meet the basic needs of an individual. This situation becomes even more worrying, when analyzed the fact that these people are unable to carry out their main activities, which are agriculture and animal husbandry, since they are totally dependent on water.